Sanitization Treatment of Fresh Produce with Acidic Electrolyzed Water: Experimental Results on Energy Efficiency, Effectiveness on Rots, Cost and Environmental Impact at Near-Industrial Scale - Ferruccio Giametta; Gianluca Tanucci; Pasquale Catalano; Antonio Ippolito; Biagio Bianchi (Sci)
This study evaluates the potential of acidic electrolyzed water (AEW) as an alternative sanitizing solution for the fruit and vegetable industry. Conducted on a near-industrial scale, the experiment used a 300 L solution with 10% AEW, measuring pH, free chlorine concentration, and electro-oxidative potential (EOP). The sanitizing efficacy of AEW was tested against common phytopathogens responsible for post-harvest decay including Penicillium expansum, Aspergillus niger, Botrytis cinerea, and Alternaria alternata. With a pH of 7.27, EOP of −0.40 mV, and free chlorine at 5 mg/L, AEW achieved an 85–90% decay reduction in a 2 min wash. Energy consumption for AEW production was notably lower than that for sodium hypochlorite, a widely used industrial sanitizer, and AEW production demonstrated a reduced environmental impact due to its recycling potential and favorable effluent properties. However, free chlorine levels necessitated further treatment before wastewater discharge.